Case Report: Severe cutaneous adverse event associated with checkpoint inhibition in the setting of CAR T-cell therapy: beyond CRS - Masucci, Chiara; Pepe, Sara; La Rocca, Ursula; Zullino, Veronica; De Propris, Maria Stefania; Barberi, Walter; Iori, Anna Paola; Martelli, Sabina; Ruberto, Franco; Martelli, Maurizio; Di Rocco, Alice (Frontiers in Oncology, 2023)
Anti-CD19 chimeric antigen receptor (CAR) T cell therapy actually represents the standard of care for multiple relapsed or refractory primary mediastinal B-cell lymphoma (r/r PMBCL). Checkpoint inhibitors, such as pembrolizumab, appear to be a safe and effective treatment strategy for patients who are ineligible for or resistant to autologous stem cell transplantation. Although preclinical studies suggested that checkpoint inhibitors may enhance the vitality and anti-tumor activity of CAR T cells, there are no substantial/robust clinical data about the immune-mediated toxicity of their association. We describe a case of a severe cutaneous adverse event arising immediately after Cytokine Release Syndrome (CRS) on day +6 from CAR T cells infusion in a young r/r PMBCL patient who previously received pembrolizumab. These skin lesions were interpreted as an immune mediated adverse event, considering their prompt improvement and fully recovering achieved with the addition of immunoglobulin infusion to systemic steroid therapy. This case of life-threatening cutaneous adverse event calls for further investigations about off-target immune-related adverse events deriving from the combination of CAR T cell therapy and checkpoint inhibition, whose synergic therapeutic effect is promising.